Carboxymethyl kappa/iota-hybrid carrageenan doped with NH4I as a template for solid bio-electrolytes development - Torres, FG (2019)
In this study, we analyzed the contribution of NH4I and glycerol on the ionic conductivity of carboxymethyl κ/ι-hybrid carrageenan-based solid bio-electrolytes. Electrochemical impedance spectroscopy was used to assess the electrochemical properties of the developed biopolymeric films and their interfaces over a wide range of frequencies (1& Hz–7& MHz). X-ray diffractograms demonstrated the increment of the amorphous fraction in the material as the NH4I content increases, suggesting an enhancement of ion transport processes and the successful incorporation of the salt into the host matrix. The shift of the OH peaks in the FTIR spectra confirmed the interaction between carboxymethyl carrageenan, NH4I, and glycerol. EIS results were represented in the complex plane and were fitted to an Rs(R1Q1) equivalent circuit. The ionic conductivity for carboxymethyl carrageenan doped with xNH4I (x = 15& wt%, 25& wt%, 35& wt%) and glycerol (15& wt%, 25& wt%) increased at higher salt and plasticizer content. This behavior was explained in terms of salt association/dissociation processes. The maximum ionic conductivity found in this study was 3.9& ×& 10−3& S/cm at room temperature. This result suggests that modified carrageenan-based materials can be suitable for the development of solid bio-electrolytes for electrochemical and energy storage applications. © 2018 Elsevier B.V.